Is Surrogate LH Surge Essential in All Induced Cycles? - Begum, Mosammat Rashida; Ehsan, Mariya; Begum, Mosammat Shahina; Khan, Farzana; Siddiqi, Maruf; Baby, Hosne Ara (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: Aim of this study was to identify the necessity of use of exogenous or surrogate LH for triggering of ovulation in induced cycles. Materials and methods: This study was conducted in Infertility Care and Research Center (ICRC) Dhaka, Bangladesh. Three hundred anovulatory patients with polycystic ovarian syndrome (PCOS) were the target population for this study. The patients were treated by different ovulation inducing agents to produce mature follicles. When follicle got the size of 18 mm or more LH was given to 150 patients (Group A) and 150 patients did not receive LH (Group B). Follicular rupture was monitored by USG. Main outcome measure was rupture of the follicle. Result: In group A 33.33% and in group B 34.67% patients responded by letrozole only, whereas 66.66% in group A and 65.34% in group B needed additional drugs like metformin glucocorticoids and gonadotropins. In both the groups response was similar in terms of number of follicular recruitment, follicular maturity, endometrial development and hormone production. Follicular rupture rate was similar in both hCG and non-hCG treated group. LUFS was detected only in 2.67% in group A and 2% cases in group B. Conclusion: If follicular development is adequate exogenous LH is not necessary for triggering of ovulation in all stimulated cycles. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13783 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 72-76